Legal Protection of Advocates' Immunity Rights - Dewi Suryandari, Wieke; Zaini, Naya Amin (International Journal of Law Social Sciences and Management, 2025)
The right to advocate immunity is the legal protection given to advocates who can practice their profession freely without the threat of criminal or civil charges. This right to immunity is regulated in Article 16 of Law Number 18 of 2003 concerning Advocates. However, the current legal protection is not yet fully effective because there is still a legal vacuum, especially in the scope of immunity rights outside the trial. As a result, advocates are still vulnerable to criminalization when performing their professional duties. This study aims to analyze the legal protection that is regulated and identify the shortcomings of regulations related to the right to advocate immunity. Using a normative legal approach, this study concludes that revisions and improvements are needed to clarify the limitations and scope of the right to immunity, including expanding the role of advocate organizations and educating law enforcement officers to prevent the criminalization of advocates.